Factors associated with the development of positive student attitudes and aesthetic response towards a South African natural environment - Opie, Frank William James (Department of Environmental and Geographical Science, 2026)
This empirical study was concerned primarily with eighteen factors that appreciably influence an individual's perceptions, aesthetic awareness and response to a natural environment - specifically that of a forest plantation. Its purpose was to identify statistically significant variables that influence aesthetic valuing within three cultures of Cape Town scholars and students and, by appropriate educational · intervention treatments, to recommend effective education strategies shown to enhance aesthetic. environmental response, ultimately contributing to a more positive attitude towards nature. An extensive search confirmed the lack of a widely recognised comprehensive theoretical model of aesthetic response to natural environments. This necessitated the blending of two existing holistic models to permit the integration of all factors identified in the literature. An instrument, consisting of seven scales based on the theories of Zuckerman, Eysenck, Feingold, Wilson, Wuthnow, Kohlberg and Maslow, was developed. The weighted significances of the various components of the adapted model were then determined for a forest context. The instruments scales were repeatedly refined, with emphasis on construct validity, retest reliability and internal consistency through five phases of pilot testing. Environmental judges and a range of scholars and students [N = 151] from differing socio-economic backgrounds were used in the pilot trials. A three-phase pre-test/post-test/postposMest administration design was adopted, and the final programme was executed in 1990 over a two month period with students from three cultures from fourteen local educational institutions. The stratified sample [N = 759} was randomly subdivided into three parallel experimental intervention fieldtrips. Two of these fieldtrips were sensory directed, focusing on visual and multi-sensory inputs respectively, and two control groups remained in the classroom, one being exposed to a televised forest trip and one serving as a non-intervention control group. The data analysis allowed the identification of a High Aesthetic Response Group of students and a Low Aesthetic Response Group within the sample as a whole. Decisively significant differences occurred between these groups in terms of the independent variables identified, namely, environmental sensitivity, environmental perception, socio-economic status [crowding in home and holiday experience] and subjective pressure from significant others. Education, age, home language, gender, urban experience, family car accessibility, television viewing time, centrality of attitude object and moral development achieved a lower level of significant difference. Field trip methods were shown to be particularly effective in enhancing the response of the Low Aesthetic Response Group students from all three cultures. When the initial low environmental sensitivity of these students is taken into account a case can be made for including tried and tested sensory directed fieldtrip activities as a fundamental part of aesthetic environmental education.